New gymnosperm wood fossils, a seed ovule structure, and a new generic affinity to cedroxylon canoasense rau from the permian and triassic jurassic of southern Brazil - Crisafulli, Alexandra María Cristina (2018)
Fil: Crisafulli, Alexandra María Cristina. Universidad Nacional del Nordeste. Facultad de Ciencias Exactas y Naturales y Agrimensura; Argentina.